The Differences of Metabolites in Different Parts of the Brain Induced by Shuxuetong Injection against Cerebral Ischemia-Reperfusion and Its Corresponding Mechanism. (29th June 2022) - Jiang, Tingyue; Jiao, Jiakang; Shang, Jinfeng; Bi, Lei; Wang, Huanhuan; Zhang, Chao; Wu, Hongwei; Cui, Yiran; Wang, Peng; Liu, Xin
Abstract : Ischemic stroke is often associated with a large disease burden. The existence of ischemia-reperfusion injury brings great challenges to the treatment of ischemic stroke. The purpose of this study was to explore the differences of metabolites in different parts of the brain induced by Shuxuetong injection against cerebral ischemia-reperfusion and to extend the corresponding mechanism. The rats were modeled by transient middle cerebral artery occlusion ( t -MCAO) operation, and the success of modeling was determined by neurological function score and TTC staining. UPLC-Q/TOF-MS metabolomics technique and multivariate statistical analysis were used to analyze the changes and differences of metabolites in the cortex and hippocampus of cerebral ischemia-reperfusion rats. Compared with the model group, the neurological function score and cerebral infarction volume of the Shuxuetong treatment group were significantly different. There were differences and changes in the metabolic distribution of the cortex and hippocampus in each group, the distribution within the group was relatively concentrated. The separation trend between the groups was obvious, and the distribution of the Shuxuetong treatment group was similar to that of the sham operation group. We identified 13 metabolites that were differentially expressed in the cortex, including glutamine, dihydroorotic acid, and glyceric acid. We also found five differentially expressed metabolites in the hippocampus, including glutamic acid and fumaric acid. The common metabolic pathways of Shuxuetong on the cortex and hippocampus were D-glutamine and D-glutamate metabolism and nitrogen metabolism, which showed inhibition of cortical glutamine and promotion of hippocampal glutamic acid. Specific pathways of Shuxuetong enriched in the cortex included glyoxylate and dicarboxylate metabolism and pyrimidine metabolism, which showed inhibition of glyceric acid and dihydroorotic acid. Specific pathways of Shuxuetong enriched in the hippocampus include arginine biosynthesis and citrate cycle (TCA cycle), which promotes fumaric acid. Shuxuetong injection can restore and adjust the metabolic disorder of the cortex and hippocampus in cerebral ischemia-reperfusion rats. The expression of Shuxuetong in different parts of the brain is different and correlated.